Penatalaksanaan Fisioterapi Pada Kasus Frozen Shoulder Akibat Capsulitis Adhesiva Sinistra Di RSUD Dr. Moewardi Surakarta - Romadhoni, Dea Linia, Sugiono S.Fis.MH.Kes (2015)
Background: Frozen Shoulder of Adhesiva capsulitis sinistra is a condition that causes the motion of the shoulder joint that often occurs without recognizable cause in which there is inflammation of the adhesive between the joint capsule, marked by an increase in pain, stiffness, and limited motion modalities given in this condition MWD, TENS, Therapeutic Manipulation Exercise and Therapy. Objective: To know the benefits modality of Micro Wave Diatermy , Transcutaneus Electrical Nerve Stimulation , manipulation therapy, exercise therapy to reduce pain, increase muscle strength, improve LGS, improve functional ability. Methods: Physiotherapy methods used in the case that the MWD modality, TENS, manipulation therapy, exercise therapy, and evaluation and measurement methods of pain (VDS), muscle strength (MMT), and measuring the LGS with Goneometer. Results: After 6 treatments showed a decrease in pain of movement T1: 6 to T6: 5nyeri press T1: 3 to T6: 2, increase muscle strength, flexor T1: 2 to T6: 3, extensor T1: 3 to T6: 5, T1 Abductor : 2 to T6: 3, and adductor T1: 2 to T6: 4, increasing active motion LGS T1 S: 30°-0-30° and T6 S: 40°-0-40°, T1 F: 30°-0-20° and T6 F : 40°-0-25°. While on passive motion T1 S: 50°-0-30 º and T6 S: 50°-0-60 º, T1 F: 0-20 º and 80º-T6 F: 90º-0-20 º, and improve functional ability . Conclusions: In the case of MWD modality, TENS, manipulation therapy, exercise therapy can decrease motion tenderness and pain, improve muscle strength, increase LGS, improve functional ability.